C.1 - Agarwal, S.P. (Meerut, 1969)
The subject of Manpower Supply is now recognised as a highly important topic for purposes of socio-economic planning. This book is a pioneering attempt to go into the concepts and methodology applicable to this field. Problems of conceptual ambiguity as witnessed in the studies made in India so far are highlighted and concrete suggestions for standardising the concepts of manpower and its supply are made. Methods currently in use are described in detail along with suggestions for developing newer and better methods to provide supply estimates which may be more relevant to the needs of manpower planning. Considerations of practicability and feasibility are not lost sight of in this study which would be of great use to planners, educationists, economists, statisticians and sociologists. The problems discussed are applicable not only to India but to a large number of countries which broadly follow the concepts laid down by the I.L.O.
Keywords: Manpower supply - Methodology